Faktor Risiko Kejadian Difteri: Cakupan Imunisasi DPT-HB-Hib 3 dan Ketersediaan Posyandu - Naura Rahma Ashila; Lucia Yovita Hendrati (Media Gizi Kesmas, 2023)
Background: Diphtheria is an infectious disease that attacks the throat and can be transmitted through droplets, direct contact with the secretions of the patient's respiratory tract or from carriers. The risk factors for diphtheria are the low coverage of DPT-HB-Hib 3 immunization and the availability of integrated healthcare center. Objectives:  To describe the distribution of diphtheria in East Java and analyze the relationship between diphtheria and its risk factors. Methods: This research evaluated the incidence of diphtheria in 38 districts or cities in East Java. The Pearson correlation test was used to analyze secondary data from the East Java Health Profile 2019-2021. The data was processed using Health Mapper and SPSS. Results: There were a correlation between DPT-HB-Hib 3 immunization and diphtheria incidence in 2019 (0.53), 2020 (0.27), and 2021 (0.34). Then there were a correlation between the availability of integrated healthcare center and diptheria incidence in 2019 (0.34), 2020 (0.25), and 2021 (0.29). Conclusions: The coverage of DPT-HB-Hib 3 immunization and the availability of integrated healthcare center were related to diphtheria incidence in East Java in 2019 but not in 2020 and 2021.